Cell and biomaterial-based approaches to uterus regeneration. Issue 3 (26th April 2019) - Liu, Feiran; Hu, Shiqi; Wang, Shaowei; Cheng, Ke
Abstract: Asherman's syndrome (AS) is an endometrial disorder in which intrauterine adhesions crowd the uterine cavity and wall. The fibrotic adhesions are primarily the result of invasive uterine procedures that usually involve the insertion of surgical equipment into the uterus. This syndrome is accompanied by a number of clinical manifestations, including irregular or painful menstruation and infertility. The most prevalent treatment is hysteroscopy, which involves the physical removal of the fibrous strands. Within the last decade, however, the field has been exploring the use of cell-based therapeutics, in conjunction with biomaterials, to treat AS. This review is a recapitulation of the literature focused on cellular therapies for treating AS.